ULTRASSONOGRAFIA DO MÚSCULO PECTORALIS MAJOR DE FRANGOS DE CORTE ACOMETIDOS POR MIOPATIAS PEITORAIS - PORFIRIO, Erique Ferreira; CASTILHO, Vivian Aparecida Rios; KOMIYAMA, Claudia Marie; SOUZA, Jacqueline Rosa; EBERHART, Bruna de Souza; SERPA, Felipe Cardoso (ANAIS DO ENIC, 2022)
-